2018
DOI: 10.26656/fr.2017.2(4).045
|View full text |Cite
|
Sign up to set email alerts
|

Influence of starter culture on the physicochemical properties of rice bran sourdough and physical quality of sourdough bread

Abstract: The effect of mixed strain culture of lactic acid bacteria (LAB) and Yeast, and yeast or L. brevis, L. plantarum, or L. sanfranciscencis on the physicochemical properties (pH, TTA, organic acid, ethanol, and sugar content) of rice bran sourdough was investigated. Starter culture with optimum physicochemical properties was used to ferment rice and wheat bran for sourdough production. Rice and wheat bran sourdough and non-fermented rice and wheat bran were mixed with wheat flour at 10% substitution level for bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…The less amylose content or the higher amylopectin content, the starch tended to absorb more water so it became more viscous (Armanda and Putri, 2015). This result consistent with the previous study reported by Hanis-Syazwani et al (2018).…”
Section: Viscosity and White Color Intensitysupporting
confidence: 94%
“…The less amylose content or the higher amylopectin content, the starch tended to absorb more water so it became more viscous (Armanda and Putri, 2015). This result consistent with the previous study reported by Hanis-Syazwani et al (2018).…”
Section: Viscosity and White Color Intensitysupporting
confidence: 94%
“…The addition of SRB to bread formulation did not influence the pH of doughs after fermentation. Similar pH values were observed in RB sourdoughs fermented with yeast or yeast combined with lactic acid bacteria [ 36 ]. According to Larsson [ 37 ], the loaf volume of baked bread increases at pH 4.65–6.15 due to the effect of dough fermentation and decreases at higher pH.…”
Section: Resultssupporting
confidence: 76%
“…Indeed, fiber content, which represents the fibrous portion of flour, does not participate to the plasticization process, while the bran content, which has plasticizable fraction, should be taken into account. The fiber, not participating directly in the plasticization reaction, was considered in the formulation only for the evaluation of absorbed water, estimated to be at 15% by weight of fiber [ 13 ]. In order to give an explanation of the adopted methodology for plasticization, a detailed recipe for the F1 sample is given as an example.…”
Section: Methodsmentioning
confidence: 99%